2015
DOI: 10.1371/journal.pone.0131118
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Vessel Sign on Susceptibility-Weighted Imaging in Acute Stroke: Prediction of Infarct Growth and Clinical Outcome

Abstract: Background and PurposePredicting the risk of further infarct growth in stroke patients is critical to therapeutic decision making. We aimed to predict early infarct growth and clinical outcome from prominent vessel sign (PVS) identified on the first susceptibility-weighted image (SWI) after acute stroke.Materials and MethodsTwenty-two patients with middle cerebral artery (MCA) infarction had diffusion-weighted imaging, SWI, MR angiography, and clinical evaluation using the National Institutes of Health Stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 37 publications
7
75
2
Order By: Relevance
“…PHVS existed not only in the hyperacute ischaemic stroke but also beyond the reperfusion window time [13, 14, 18, 21, 22]. However, the relationship between PHVS beyond the reperfusion window period and clinical outcome remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PHVS existed not only in the hyperacute ischaemic stroke but also beyond the reperfusion window time [13, 14, 18, 21, 22]. However, the relationship between PHVS beyond the reperfusion window period and clinical outcome remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies revealed that PHVS occurred beyond the reperfusion window time that was related to poor outcome, while some studies found that PHVS was not associated with the 3-month prognosis [13, 18, 21, 22]. The current study substantiated that PHVS correlated with the poor outcome beyond the reperfusion window, which might be attributed to the following reasons: The patients who underwent SWI after the window of reperfusion therapy presented PHVS that represented misery perfusion [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Susceptibility-weighted imaging is useful for evaluating cerebral veins in AIS because it is extremely sensitive to paramagnetic substances such as deoxyhemoglobin, thus reflecting the oxygen extraction fraction and the cerebral metabolic rate of oxygen of the hypoxic tissue. [1][2][3][4] Shortly after vascular occlusion, the uncoupling between oxygen supply and demand in the hypoperfused region leads to an elevated oxygen extraction fraction and subsequent increased level of deoxyhemoglobin in the vessel, which contributes to prominent hypointensity of the draining veins on SWI. [5][6][7] Asymmetric cortical veins, which can be visualized on SWI after AIS and are considered an indicator of salvageable ischemic penumbra, were found to be associated with 3-month outcome.…”
mentioning
confidence: 99%